Bile Reflux Gastritis: Insights into Pathogenesis, Relevant Factors, Carcinomatous Risk, Diagnosis, and Management - Xiaolan Shi; Zijiao Chen; Yi Yang; Su Yan (Gastroenterology Research and Practice)
Bile reflux gastritis (BRG), a kind of gastrointestinal disorder in clinical practice, is characterized by regurgitation and inflammation. However, lack of guidelines leads to simple cognition and even ignorance of this disease for clinicians. Primarily, making the pathogenesis of BRG clear contributes to a correct and general understanding of this disease for physicians. Next, although recently there has been an increasing awareness among researchers in terms of the relevant factors for BRG, further studies involving large samples are still required to certify the relationship between them explicitly. Besides, researches have established that BRG is closely associated with the development of precancerous lesions and gastric cancer. Till now, there is still no golden standard for diagnosis of BRG. Nevertheless, advances in techniques, especially extensive applications of endoscopy and chemical analysis of reflux contents, have improved our ability to identify the occurrence of this disease as well as distinguishing physiological reflux from pathological reflux. Finally, it is fortunate for patients that more and more importance has been attached to the treatment of BRG. From lifestyle modification to drug therapy to surgery, all of them with the view of realizing symptomatic relief are employed for patients with BRG. In this review, we briefly evaluate this disorder based on the best available evidence, offering an overview of its complicated pathogenesis, diverse relevant factors, potential carcinomatous risk, modern diagnostic investigations, and effective therapeutic plans.